A water-activated paper-based battery based on activated carbon powder anode and CuCl2/CNT cathode. (December 2020) - Nguyen, Dang-Trang; Ito, Yosuke; Taguchi, Kozo
Abstract: Water-activated paper-based batteries are expected to be low-cost disposable power sources for paper-based sensor applications. In this study, a disposable paper-based battery was developed. The battery used activated carbon powder loaded on a carbon sheet as the anode. The cathode was coated directly on a paper filter to fabricate an integrated proton exchange membrane cathode. Copper (II) chloride mixed with multiwalled carbon nanotube (CuCl2 /CNT) was used as the cathode. Water was injected into the anode electrode to activate the battery. The maximum power density of 134. 6 μ W /cm 2 was obtained with the anode loaded 17 mg cm −2 activated carbon powder. The power output of the battery is proportional to the amount of activated carbon loaded on the anode.